Circadian acclimatization of performance, sleep, and 6-sulfatoxymelatonin using multiple phase shifting stimuli - Youngstedt, Shawn D.; Elliott, Jeffrey; Patel, Salma; Zi-Ching Mak, Natalie; Raiewski, Evan; Malek, Elias; Strong, Michael; Mun, Chung Jung; Peters, Tyler; Madlol, Remun; Tasevska, Natasha; Rasoul, Massiullah; et al. (Frontiers in Endocrinology, 2022)
Misalignment between the environment and one’s circadian system is a common phenomenon with myriad negative effects on health, performance, and sleep. Absent any intervention, the circadian system adjusts only 0.5-1.0 h per day to a shifted light-dark and sleep-wake schedule. Bright light facilitates circadian adjustment, but in field studies, it is only modestly better than no stimulus. Evidence indicates that exercise and melatonin can be combined with bright light to elicit larger shifts. No study has combined all of these stimuli or administered them at the times that are known to elicit the largest circadian effects. The study aims are to compare the effects of different treatments on circadian adjustment to simulated jet lag. Following 2 weeks of home recording, 36 adults will spend 6.5 days in the laboratory. Following an 8 h period of baseline sleep recording on Night 1, participants will undergo a 26 h circadian assessment protocol involving 2 h wake intervals in dim light and 1 h of sleep in darkness, repeated throughout. During this protocol, urine voidings will be collected; mood, sleepiness, psychomotor vigilance, and pain sensitivity will be assessed every 3 h,, and anaerobic performance will be tested every 6 h. Following, the circadian assessment, the sleep-wake and light dark schedule will be delayed by 8 h, analogous to 8 times zones westward (Figure 4). This shifted schedule will be maintained for 3 days (Figure 4), during which participants will be randomized to: (1) Dim Red Light + Placebo Capsules, (2) Bright Light Alone, or (3) Bright Light + Exercise + Melatonin. During the final 26 h, the circadian assessment protocol, will be repeated. . Acclimatization will be defined by shifts in circadian rhythms of aMT6s, psychomotor vigilance, anaerobic performance, mood, and sleepiness, and less impairments in these measures during the shifted schedule vs. baseline. We posit that Bright Light Alone and Bright Light + Exercise + Melatonin will elicit greater rhythm shifts and less impairments in sleep, mood, performance vs Dim Red Light + Placebo, and Bright Light + Exercise + Melatonin will elicit greater shifts and less impairments than Bright Light Alone.